Coady, Amanda. L to R Tom Coady, Debbie Coady, Unknown, Marlee Coady and Tommy Boland at Lance Cove on the beach. - Heritage NL
Amanda Coady provided a picture of (from left to right) Tom Coady, Debbie Coady an unidentified person, Marlee Coady and Tommy Boland on a sandy beach in Lance Cove. Tom Coady sits on a jacket beside Debbie Coady who sits on a blanket, both facing away from the camera. Tom Coady is holding a blue cup. Beside Debbie Coady is another blanket on which can be found a blue cup, children's blue and white sneakers and a patterned grey white and brown cardigan; to the right of which is a beige and brown jug. Further from the camera the unidentified individual, Marlee Coady and Tommy Boland are gathered around a camping table, seemingly preparing food that appear to be sandwiches. To their left in frame, on the beach, lay a number of paper bags and other assorted detritus, including a Maxwell House box and a blue cup. In the background is an orange dory attatched to a green cord.